1994
DOI: 10.1210/endo.135.5.7525257
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of postnatally elevated insulin-like growth factor-II in transgenic mice: endocrine changes and effects on body and organ growth.

Abstract: Insulin-like growth factor-II

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 39 publications
4
35
0
Order By: Relevance
“…Also IGF2 seems to have specific effects for adrenal growth and function. Although body weight was not significantly affected in mice overexpressing IGF2, the adrenal glands in these transgenic mice showed significant increases in weight ( Wolf et al 1994, Weber et al 1999. In summary, several components of the GH/IGF1 system potently influence growth and function of the mouse adrenal gland.…”
Section: Gh/igfmentioning
confidence: 86%
“…Also IGF2 seems to have specific effects for adrenal growth and function. Although body weight was not significantly affected in mice overexpressing IGF2, the adrenal glands in these transgenic mice showed significant increases in weight ( Wolf et al 1994, Weber et al 1999. In summary, several components of the GH/IGF1 system potently influence growth and function of the mouse adrenal gland.…”
Section: Gh/igfmentioning
confidence: 86%
“…Furthermore, adult IGF-II serum levels are very high (700 ng/ml), and the biologically active fraction that is not bound to IGFBPs might be large enough to exert an endocrine effect in the adrenal gland (Humbel 1990). An endocrine effect of elevated levels of IGF-II on the adrenal gland has recently been suggested by the findings of Wolf et al (1994), who reported an increased adrenal weight in transgenic mice that develop elevated serum levels of IGF-II postnatally (Wolf et al 1994). Adult bovine and human adrenocortical cells therefore represent a useful model system to help us to investigate the complex interaction of two IGF ligands, two IGF receptors, six IGFBPs and at least as many IGFBP-specific proteases.…”
Section: Discussionmentioning
confidence: 99%
“…While GH-over-expressing mice exhibit increased kidney size and hypertrophy [27], IGF-I over-expression results in hyperplasia [28] and increased glomerular size [27,29] indicative of distinct effects of GH and IGF-I on kidney growth or development. IGF-II over-expression also results in an overall increase in kidney size [30,31]. IGF-I-deficient animals display particular muscle hypoplasia [24], and IGF-I excess results in skeletal muscle hypertrophy [32].…”
Section: The Gh-igf-i Axis In Modulating Growth and Organ Developmentmentioning
confidence: 99%